The Correlation Results of Examination of Hemoglobin and The Erythrocyte Index in Patients With Suspected Covid-19 in The Hospital of Kendari City - Sri Aprilianti Idris; Firdayanti Firdayanti; Susanti Susanti; Muh. Azdar Setiawan (JURNAL INDONESIA DARI ILMU LABORATORIUM MEDIS DAN TEKNOLOGI, 2022)
Coronavirus disease 2019 has become a global problem causing hundreds of thousands of deaths worldwide. Haemoglobin is more susceptible to COVID-19 virus attacks. Haemoglobin functions as a carrier of oxygen to organs in the body. When the concentration of haemoglobin in the blood circulation is low, the transport of oxygen to several organs in the body can be disrupted. SARS-CoV-2 interacts with haemoglobin in red blood cells. This interaction causes the virus to break the haemoglobin chain and cause hemolysis. The erythrocyte index which consists of MCV, MCH, and MCHC values ​​is used to indicate the occurrence of anemia in COVID-19 patients. This research method used descriptive analytic with a cross sectional study design. The population of this study was suspected COVID-19 patients with a sample of 27 people. Sampling was carried out using purposive sampling. This study aims to determine the relationship between haemoglobin examination results and erythrocyte index in suspected COVID-19 patients.The instrument in this study used secondary data which included the results of examination of haemoglobin values ​​and erythrocyte index. The results of the test using a parametric statistical approach with the correlation analysis method showed that there was a correlation between the results of the haemoglobin and MCV test (P-value 0.057 > 0.05), while the haemoglobin and MCH test had no correlation (P value 0.777 > 0.05), and there is no correlation between haemoglobin and MCHC examination (P-value 0.372 > 0.05).